Distance of brachiaria management in between the rows of coffee trees - Franco Junior, Kleso Silva; Calegari, Ademir; Dias, Marcio de Souza; Brigante, Giselle Prado (Revista Brasileira de Engenharia de Biossistemas, 2023)
Brazil is the world’s largest coffee producer, but with the changes in climate that have occurred in recent years, the concern with soil management with cover crops has become important, since it configures a strategy that can contribute to the improvement of production systems. Brachiaria is one of the main species used in intercropping in coffee production to generate biomass and soil cover. The objective of this research was to evaluate the effect of the distance of brachiaria management in between rows of coffee trees. The research was carried out from 2016 to 2022 in a coffee plantation implanted in 2016 with the cultivar Catuai Amarelo IAC 62 associated with Brachiaria ruziziensis, in a randomized block design, with 6 treatments and 4 replications: T1- without brachiaria between the rows (control), T2 - management of brachiaria up to the projection of the coffee tree crown, T3 - management with 25 cm distance from the projection of the crown of the coffee tree, T4 - management with 50 cm away from the projection of the coffee tree crown, T5 - management with 75 cm distance from the projection of the coffee tree crown, T6 - management with 100 cm distance from the projection of the coffee tree crown. The evaluated parameters were: setting and establishment of coffee seedlings, height of the orthotropic branches, length of the plagiotropic branches, number of internodes, and productivity. The intercropping of the coffee tree with brachiaria must be managed at 50 cm from the projection of the plagiotropic branch of the coffee tree, aiming at non-competition and better development of the crop.